Commercial baby foods aimed at children up to 36 months - Santos, Mariana (2022)
Proper nutrition in infancy and early childhood is crucial to ensuring optimal child development, growth, and better health outcomes later in life. The nutrient profile model proposed by WHO/Europe aims to assess the nutritional quality and promotional/marketing aspects of commercial baby foods aimed at children up to 36 months. We used commercial data from 191 baby foods collected between March 2021 and July 2021, from eight supermarket chains in the Lisbon Metropolitan area. According to the model specifications and the NOVA classification system, we assessed the nutritional quality and promotion aspects and the degree of processing, respectively. The presence of at least one sugar-contributing ingredient was found in 34.0% of the products; 13.9% of products listed sugars and 15.0% listed fruit juices or concentrates as an ingredient. The claim "No added sugar" was present in 69.6% of products. Only 35.1% of products comply with all the nutritional requirements of the model. Concerning processing classification, 61.8% of products were ultra-processed, and about 57.0% were indicated for children < 12 months. These findings reinforce the importance of implementing measures to ensure that commercial foods for infants are marketed appropriately and to promote foods with a lower degree of processing.